The impact of linguistic vs. cultural imperialism on language learning - Razmjoo Moghadam, Somayeh; Barani, Ghasem (Frontiers in Psychology, 2025)
The current study systematically reviewed selected literature on background, current conceptualization, and direction of the issues of linguistic and cultural imperialism in publications of applied linguistics and language teaching to determine themes in the field. To do this, based on the inclusion/exclusion criteria, provided in the PRISMA Chart, 30 most updated and recent articles (mainly since 2020) were selected from the 5 main publications in the field through the advanced search engines. Then, two raters used coding books to screen and code necessary quantitative and qualitative data based on which, a total of 989 general coding schemes and categories were elicited from the coding of the main themes, trends, and findings of linguistic and cultural imperialism. Overall, the main themes of the study were provided in the form of the concepts and perspectives of linguistic and cultural imperialism, informed by the historical directions and the influence of the colonial era. Moreover, the role of power relations and prevailing linguistic dominance in supporting dominant languages and the influence of linguistic and cultural imperialism on L1 acquisition were presented and discussed. Since language imperialism can impact L1 language acquisition by marginalizing local languages and threatening them, each community needs to follow its practical language policy and plans to revitalize and support its languages and cultures. It was suggested that the intersection of linguistic and cultural imperialism impacts social and language identity which can lead to neo-imperialism, colonization, and language hierarchization. The study puts forward some recommendations and suggests future directions to reinforce language rights through different parties with the integration of a human rights perspective in language preservation efforts as the main actions that can be done to improve language awareness of the people. Policy-makers and language decision-makers can follow these guidelines to preserve the legal aspects of the language and cultural identity and utilize foreign languages in more rational and non-threatening ways.